2019
DOI: 10.21153/jtlge2019vol10no1art785
|View full text |Cite
|
Sign up to set email alerts
|

Integrating career development learning into the curriculum: Collaboration with the careers service for employability

Abstract: Career development learning has a demonstrable positive impact on the graduate employability of higher education learners. This is particularly the case if it is integrated into the curriculum rather than experienced as an add-on or included in finite curriculum elements. However, integration of career development learning into curriculum is a significant and challenging undertaking in course design, and also in facilitation of learning experiences. Academics manage crowded curricula in their disciplinary area… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
69
1
2

Year Published

2019
2019
2024
2024

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 60 publications
(76 citation statements)
references
References 19 publications
4
69
1
2
Order By: Relevance
“…To some degree there is an expectation that a university degree will least help students develop employability skills. Prior literature on this topic also reveals that "career development learning has a demonstrable positive impact on the graduate employability of higher education learners" (p. 56, Bridgstock, Grant-Imaru, & McAlpine;. However, the finding of this study reveals that the responsibility for employability skill development was not wholly considered to be the responsibility of faculty members.…”
Section: Summary Discussion and Conclusioncontrasting
confidence: 59%
“…To some degree there is an expectation that a university degree will least help students develop employability skills. Prior literature on this topic also reveals that "career development learning has a demonstrable positive impact on the graduate employability of higher education learners" (p. 56, Bridgstock, Grant-Imaru, & McAlpine;. However, the finding of this study reveals that the responsibility for employability skill development was not wholly considered to be the responsibility of faculty members.…”
Section: Summary Discussion and Conclusioncontrasting
confidence: 59%
“…Undergraduate career development is more likely to be successful if it is in-curriculum, assessed and course-wide (Bridgstock, 2009;Bridgstock, Grant-Imaru, & McAlpine, 2019). Indeed, in-curriculum undergraduate career development programs have been associated with reductions in unemployment, job-search times and with improved engagement with career development (Ciarocco, 2018;Hughes, Bosley, Bowes, & Bysshe, 2002;Thomas & McDaniel, 2004).…”
Section: How To Effectively Engage Undergraduates With Their Career Dmentioning
confidence: 99%
“…There are limited published studies of undergraduate in-curriculum career development programs and their impacts on students' career awareness or employability, and even less that focus on nonvocational degrees (Bridgstock et al, 2019). In a 2018 review of published in-curriculum approaches to career preparation and professional development for US undergraduate psychology majors, it was reported that they lead to students having a better understanding of psychology-related careers, are more knowledgeable about how to access career information and are more likely to exhibit career information seeking behaviour (Ciarocco, 2018).…”
Section: Do Other Undergraduate In-curriculum Career Development Progmentioning
confidence: 99%
“…A number of theorists have pointed out the advantages of a "processual" approach (Holmes, 2001) to researching employability, and also to employability learning itself (Bridgstock, Grant-Iramu, & McAlpine, 2019;Jackson, 2016;Tomlinson, 2017). By viewing employability as a process of sense-making, discovery, and selfconstruction (Savickas, 2011), a wide range of internal and external influences including skill development can be explored in context, through a subjective lens.…”
Section: The Importance Of the Student's Perspectivementioning
confidence: 99%